Colony Nutrition Enhances Bee Resilience to Fungicides, While the Benefit of Propolis Supplementation Depends on Stress Conditions - Yara Martins Molina Ferraz; Aline Yukari Kato; Tainá Angelica de Lima Freitas; Cássia Regina de Avelar Gomes; Thais Regina Ramos Alves; Matheus Franco Trivellato; Samir Moura Kadri; Ricardo de Oliveira Orsi; David De Jong; Jaqueline Dalbello Biller; Daniel Nicodemo (Agriculture)
Enhanced colony nutrition can support brood development, resulting in better physiological conditions and increased resilience in adult honey bees, particularly under stress. This study investigated the effects of colony nutrition and adult dietary supplementation with green propolis on bee health under fungicide exposure. Colonies were managed under food restriction or nutritional supplementation for 22 weeks. Newly emerged bees from each colony were then caged and fed protein diets consisting of honey-pollen patties contaminated or not with fungicide, and sucrose sugar syrup with or without aqueous green propolis extract. Bees from supplemented colonies showed greater body weight, higher hemolymph protein levels, and higher consumption of protein food after seven days in cages. Fungicide exposure reduced hemolymph protein levels, altered the expression of detoxification and immune-related genes, and significantly decreased bee survival. Interestingly, propolis supplementation alone changed gene expression patterns and slightly reduced longevity compared to bees not exposed to propolis or fungicide. However, under fungicide stress, bees that ingested propolis survived longer, indicating a protective effect. While colony nutritional supplementation clearly promotes honey bee resilience against fungicide exposure, feeding propolis also showed promising effects, though further studies are needed to determine an optimal dietary concentration.